2020
DOI: 10.1002/hup.2767
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Korean red ginseng on human gray matter volume and cognitive function: A voxel‐based morphometry study

Abstract: Objective: We aimed to investigate the effects of Korean red ginseng (KRG) supplementation on gray matter volume of the human brain which could be related to cognitive enhancing effects of KRG. Methods: In this randomized, double-blind, placebo-controlled study, 51 healthy individuals were assigned to receive either KRG (1000 mg/day, n ¼ 26) or placebo (n ¼ 25) for 8 weeks. Gray matter volume of the whole brain was measured using voxel-based morphometry based on high-resolution T1-weighted magnetic resonance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…In this study, our emphasis was specifically placed on memory function as the primary cognitive domain of interest, a focus motivated by the fact that memory is one of the earliest cognitive domains impacted by T2DM [ 33 , 34 ]. It is imperative, however, to acknowledge that cognitive dysfunction associated with T2DM may encompass various domains, including executive function, processing speed, and motor function, particularly as the disease advances [ 4 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, our emphasis was specifically placed on memory function as the primary cognitive domain of interest, a focus motivated by the fact that memory is one of the earliest cognitive domains impacted by T2DM [ 33 , 34 ]. It is imperative, however, to acknowledge that cognitive dysfunction associated with T2DM may encompass various domains, including executive function, processing speed, and motor function, particularly as the disease advances [ 4 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ROCF, a commonly used neuropsychological test, examines the integrity of visual memory and visuospatial constructional ability [ 31 , 32 ]. The CVLT serves as another widely accepted neuropsychological assessment, measuring verbal memory and episodic learning [ 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…Several pharmacological approaches have been widely used for intervening in AD-related CI, e.g., cholinesterase inhibitors and memantine. Meanwhile, ginseng and its main extract ginsenosides already show their protective effect on AD-associated CI in a few well-designed randomized controlled trials [ 11 , 44 , 45 , 46 , 47 ] ( Table 2 ). A series of clinical studies were conducted by Heo [ 11 ].…”
Section: Protective Effect Of Ginsenosides On CImentioning
confidence: 99%
“…In another randomized controlled trial, 97 individuals were orally treated with Panax ginseng powder (which contains a total of 8.19% of ginsenosides) at a dose of 4.5 g/d or 9 g/day; the results demonstrated that ginsenosides supplement can increase the Alzheimer’s Disease Assessment Scale (ADAS) and Mini-Mental State Examination (MMSE) score, which revealed the improvement of cognitive function [ 45 ]. Furthermore, in a randomized, double-blind, placebo-controlled study, it was demonstrated that Korean red ginseng (KRG) administration at a dose of 1000 mg/day for 8 weeks can increase the gray matter volume and composite cognitive scores of healthy individuals [ 46 ].…”
Section: Protective Effect Of Ginsenosides On CImentioning
confidence: 99%
“…Meyer (here termed ginseng) has been used for thousands of years to treat diseases and to help maintain the body's homeostasis [13,14]. The active components of ginseng are ginsenosides, polysaccharides, and polypeptides, and their pharmacological activities including anti-fatigue, anti-cancer, and immune enhancement effects have been previously reported [15,16]. Ginseng products are referred to by various terms, depending on the processing method: freshly harvested ginseng is termed fresh ginseng, dried ginseng is referred to as white ginseng, and steamed dried ginseng is termed red ginseng [17,18].…”
Section: Introductionmentioning
confidence: 99%